Análisis de películas biopoliméricas de almidón para potencial aplicación en optoelectrónica. - Hariana Farfán Benavides; Karol Roa Bohórquez; Raúl Sánchez Alarcón; Ricardo Paredes Roa (Mundo Fesc)
Research into energy-efficient materials, such as perovskites, has increased due to their characteristics, low cost, and variety of production methods, which allow for the development of optoelectronic devices. However, their susceptibility to instability when exposed to air, humidity, or temperature variations has motivated the search for alternative structures that utilize sustainable materials, thereby seeking to improve their durability, optimize manufacturing, and reduce costs. In this context, the synthesis of a starch polymer matrix using a biopolymer is proposed, with the aim of mitigating the use of hydrocarbon-based polymers. The selected polysaccharides come from potatoes and aquatic plants from Lake Tota (Elodea). They were dissolved in dimethyl sulfoxide and dimethylformamide under ambient conditions, evaluating the feasibility of their application in technologies that employ perovskites. The process resulted in the production of homogeneous films, demonstrating the partial and complete dissolution of starches and thus laying the groundwork for their potential application in these perovskite-based devices.